Pengaruh Pemberian Topikal Madu Kaliandra Terhadap Jaringan Granulasi Pada Luka Diabetes Melitus - Nengke Puspita Sari; Maritta Sari (Universitas Mitra Indonesia, 2020)
Diabetes mellitus most often causes complications, namely the presence of injuries to the feet due to pathological changes in the limbs. Wounds are a malfunction and normal anatomical structure, whereas wound healing is a complex dynamic process that results in improved function and anatomical continuity. This study aims to determine the effect of topical application of Kaliandra honey with tissue granulation on diabetes mellitus wounds. The analytical survey research method uses a quasi-experimental approach. Tissue granulation assessment was carried out before and after calliandra honey therapy. The results showed that there was a significant difference between the amount and color of the tissue before and after calliandra honey therapy. Calliandra honey therapy is effective in the growth of granulation tissue in diabetes mellitus wounds.Keywords : tissue, calliandra honey, diabetes, granulation